(untitled) (MAUSAM, 2016)
The effect of topography on June to August (JJA) rainfall over east Africa is investigated using the International Centre for Theoretical Physics (ICTP) Regional Climate Model (RegCM4.0). Grell convection scheme with Fritsch-Chappell closure assumption is used. The control simulation is done with actual topography and sensitivity experiments are carried out with topography reduced to 75%, 25% and to zero. The model output was evaluated against Climate Research Unit (CRU) dataset, gridded at 0.5 degree resolution and ERA-interim datasets, gridded at 0.75 degree resolution. Results show that the mean JJA rainfall significantly reduces over the region when topography elevation is reduced. Based on the model, when the topography over the selected region (KTU) is reduced to 25%, the mean JJA rainfall over east Africa is reduced by roughly half. The maximum rainfall reduction is however observed around the region over which topography is reduced. The reduction in topography resulted into an anomalous moisture divergence over the region at low level (850 hPa). Divergence at low level results in vertical shrinking which suppresses convection due to subsidence. The strength of moisture transport and the zonal wind speed at 850hpa increased with decrease in topography, which may be responsible for the observed shift in moisture convergence zone from western Kenya to northern Uganda. The findings from this study would provide insight into the effect of topography on the east African climate and call for more detailed investigative research, particularly in the region. The results may motivate researchers and modeling centers to further improve on the performance of the model over the region.